Digesting Faeces at Household Level - Experience From a “Model Tourism Village” In South India - Christian Zurbrügg, Yvonne Vögeli and Nicolas Estoppey
The scope of the study was to assess the strengths and weaknesses of existing household level biogas systems treating toilet waste as well as organic kitchen waste. The biogas systems studied had been implemented on Kumbalangi Island in South India within the framework of a Tourism Development Project to improve sanitary conditions. The assessment comprised a technical monitoring of two selected facilities over a period of two months as well as a household level users survey. Results reveal that the systems are working quite satisfactorily and are generating enough biogas to cook the main dishes of a family along with replacing most of the traditional cooking fuel. The treatment efficiency of the organic pollution is as good as to be expected from biogas systems. However, the effluent does not match the legal requirements for use without any restrictions as organic fertilizer or for discharge into surface water bodies without any further treatment. The current investment costs are high as subsidies formerly provided are not available anymore. This severely limits the potential of wide spread replication.